2020
DOI: 10.3390/vaccines9010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four SARS-CoV-2 Neutralization Assays

Abstract: Neutralizing antibodies are a major correlate of protection for many viruses including the novel coronavirus SARS-CoV-2. Thus, vaccine candidates should potently induce neutralizing antibodies to render effective protection from infection. A variety of in vitro assays for the detection of SARS-CoV-2 neutralizing antibodies has been described. However, validation of the different assays against each other is important to allow comparison of different studies. Here, we compared four different SARS-CoV-2 neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 26 publications
(35 reference statements)
6
117
0
Order By: Relevance
“…Importantly, our studies rely on pseudoviruses, which are only capable of modeling the ACE2-dependent entry step of the SARS-CoV-2 life cycle. While numerous studies have now demonstrated a close correlation between neutralization titers measured against pseudovirus and live SARS-CoV-2 cultures (Wang et al, 2020;Ju et al, 2020;Pinto et al, 2020;Yang et al, 2020;Moore et al, 2004;Crawford et al, 2020;Riepler et al, 2020), it is unclear what impact additional mutations located outside of the spike may have on immunological escape, virulence, infectivity, or pathogenesis. Several recent reports and preprints, including studies conducted by Pfizer as well as Moderna, have produced similar findings in terms of vaccine potency against B.1.1.7 and B.1.1.298 variants but substantially less neutralization resistance by B.1.351 than we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our studies rely on pseudoviruses, which are only capable of modeling the ACE2-dependent entry step of the SARS-CoV-2 life cycle. While numerous studies have now demonstrated a close correlation between neutralization titers measured against pseudovirus and live SARS-CoV-2 cultures (Wang et al, 2020;Ju et al, 2020;Pinto et al, 2020;Yang et al, 2020;Moore et al, 2004;Crawford et al, 2020;Riepler et al, 2020), it is unclear what impact additional mutations located outside of the spike may have on immunological escape, virulence, infectivity, or pathogenesis. Several recent reports and preprints, including studies conducted by Pfizer as well as Moderna, have produced similar findings in terms of vaccine potency against B.1.1.7 and B.1.1.298 variants but substantially less neutralization resistance by B.1.351 than we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Samples testing positive in one or both of the assays above were additionally analyzed using an in-house neutralization assay based on a replication-defective vesicular stomatitis virus (VSV) vector, which was pseudotyped with a C-terminally truncated version of the spike protein of SARS-CoV-2 (Wuhan isolate), [11] VSV∆G-S, as previously described [12]. Briefly, serial 1:4 dilutions of heat-inactivated plasma (starting at a 1:16 dilution) were pre-incubated with the virus for 1 h at 37 • C. Subsequently, they were used to infect 293 T-cells seeded the previous day.…”
Section: Neutralization Assaymentioning
confidence: 99%
“…These trials are evaluating the potential therapeutic benefit of IVIg for treatment of SARS-CoV-2 infection in both hospitalized and ambulatory patients. Further, considerable effort by the World Health Organization (WHO) and others has focused on correlating data from a range of SARS-CoV-2-specific ELISAs to neutralization assays with the objective of understanding both the diagnostic and predictive value of these and other point-of-care diagnostic tools [ 24 , 25 , 26 , 27 , 28 ]. Although neutralization assays, including the one described here, are not typically used as diagnostic tools, we showed that our assay correlates well with a commonly used diagnostic ELISA.…”
Section: Discussionmentioning
confidence: 99%